A Rare Case of Traumatic Bilateral Fibular Head Fractures - Anastasios Chytas; Antonios Spyridakis; John Gigis; Theodoros Beslikas; Nikolaos Panos; John Christoforidis (Case Reports in Medicine)
Avulsion fibular head fractures are rare. There is only one reference of bilateral fibular fractures after epileptic seizure. We aim to present the mechanism and the treatment of this rare injury. We present the case of a 30-year-old woman who was hit by a car on the anteromedial side of both knees. Clinical and radiographic control showed bilateral fibular head fractures. Knee instability was not found at both knees and MRI did not show any concomitant ligament ruptures. Bone bruises of both medial condyles found in MRI explain the mechanism of this injury. The patient was treated conservatively with functional knee braces for 6 weeks allowing full range of motion, but otherwise mobilised as normal without any support. Six weeks after the trauma, there were no symptoms while the fractures sites had united completely after 6 months. One year postinjury the patient was free from symptoms.